Pharmacy practice research in Saudi Arabia; A bibliometrics analysis from (2000 to 2021) - Fawaz Mutlaq Alotaibi; Abdulaziz Abdullah Almotlak; Shakil Ahmad (Elsevier, 2022)
Background: Pharmacy is a growing profession in the Kingdom of Saudi Arabia which has experienced tremendous changes in the past 20 years. Pharmacy practice or clinical pharmacy have an attention ever since the emerging of PharmD programs throughout the Saudi universities. As a result, the number of affiliated faculty in the pharmacy practice departments has increased dramatically in the past 20 years and thus significant changes in research output were observed. Objectives: The main objective is to conduct a bibliometric analysis and evaluate the research output of pharmacy practice faculty in Saudi Universities from 2000 to 2021 Methods: A systematic search was conducted using Scopus database to explore the research output from pharmacy practice affiliated faculty from 2000 to 2021. The following search terms AFFILORG ("Pharmacy Practice Department" OR "Department of Pharmacy practice" OR "Clinical Pharmacy Department" OR "Department of Clinical Pharmacy" OR "Department of Pharmacy Services") AND AFFILCOUNTRY ("Saudi Arabia" OR "KSA" OR "Kingdom of Saudi Arabia") were used. Only original research papers were retrieved and analyzed using MS Excel (v16.0), MS Access (v16.0), Bibexcel (v2017), VOS viewer, and Biblioshiny. Results: In the past two decades, most publications with pharmacy practice departments affiliation were pharmacy practice research irrelevant (only 1075 out of 2809). King Saud University and King Abdulaziz University were the top performing institutes, and median of 5-year impact factor for journals was more than 3 for most of the top 10 institutes. 19% of the total retrieved articles were review publications were the rest majorly classified as cross-sectional studies. Conclusion: The research contribution of pharmacy practice departments in Saudi Arabia has been improving. Key recommendations are to promote more applied and interventional research, increase publications in top journals, and enhance national collaborations.